Análise de intervenções para adequação do nível de serviço em rodovias de pista simples com base no HCM - Igor Vieira Santos (2022)
When operational problems occur on two-lane rural highways, many managers consider duplication the main option. However, configurations such as passing lanes and "2+1" roads are intermediate solutions widely used in other countries to improve operational conditions. Thus, the main objective of this dissertation was to a nalyze the operational conditions and the feasibility of widening interventions of two-lane rural highways, such as: i) passing lanes; ii) 2+1 road; iii) duplication. The proposed method has two main steps: i) data collection and treatment; ii) operational analysis by determining the levels of service using the 6th (HCM 2016) and 7th (HCM 2022) editions of the Highway Capacity Manual (HCM). To indicate a widening intervention, the passing lanes were analyzed with a length of approximately 1.60 km and minimum spacing of 3.0 km. The results were obtained considering a traffic demand of 6.352 veh/day and 626 veh/h in the first year of operation, using a growth rate of 3% to prospect the traffic volumes along the project period. The results obtained by applying the HCM 2022 indicated that the passing lanes could promote one level of service improvement lasting for seven to ten years. Similarly 2+1 highways can improve the operational conditions for 16 years, and highway duplication is unnecessary during this period. In the 2016 HCM, the terrain classification in level or rolling can produce a difference of one level of service. Segments with level terrain presented results that take an average of six years to be equivalent to those obtained for segments with rolling terrain. Regarding the comparison of the results of the level of service obtained with HCM 2022 and HCM 2016, it was possible to observe a difference of two levels of service, with HCM 2022 presenting better levels of service. The difference to achieve the level of service "D" for rolling terrain with both manuals was 20 years.